Epitheliotropic Infections in Wildlife Ruminants From the Central Alps and Stelvio National Park - Gallina, Laura; Savini, Federica; Casà, Giovanni; Bertoletti, Irene; Bianchi, Alessandro; Gibelli, Lucia Rita; Lelli, Davide; Lavazza, Antonio; Scagliarini, Alessandra (Frontiers in Veterinary Science, 2020)
The mountain chain of the Alps, represents the habitat of alpine fauna where the red deer (Cervus elaphus) population is the outmost numerous, followed by the chamois (Rupicapra rupicapra) and the alpine ibex (Capra ibex) at higher altitudes. Previous reports showed the circulation of epitheliotropic viruses, belonging to the families Papillomaviridae and Poxviridae, causing skin and mucosal lesions in wild ruminants of the Stelvio National Park, situated in the area. To deepen the natural dynamics of the infections, a passive surveillance on all the cases of proliferative skin and mucosal lesions in wild ruminants was performed. Twenty-seven samples (11 chamois, 10 red deer and 6 ibex) collected from 2008 to 2018 were analyzed by negative staining electron microscopy, histology and PCR followed by genome sequencing and phylogenetic analyses. Results confirmed the spread of PVNZ in Italy, and its ability to cause severe lesions i.e. erosions and ulcers in the mouth. We showed for the first time a PVNZ/CePV1v co-infection identified in one red deer. This result supports previous evidence on the ability of papillomavirus and parapoxvirus to mutually infect the same host tissue. Interestingly two ibex and one chamois showing orf virus (OV) skin lesions were shown to be co-infected with bovine papillomavirus type 1 and 2. The presence of bovine papillomavirus, in orf virus induced lesions, chamois and ibex raises the question of its pathogenetic role in these animal species. For the first time, OV/CePV1v co-infection was demonstrated in another chamois. CePV1v is sporadically reported in red deer throughout Europe and is considered species specific, its identification in a chamois suggests its ability of cross-infecting different animal species. Poxviruses and papillomavirus have been simultaneously detected also in the skin lesions of cattle, bird and human suggesting a possible advantageous interaction between these viruses. Taken together, our findings add further information on the epidemiology and pathogenetic role of epitheliotropic viruses in wild ruminants living in the central Alps and in Stelvio National Park.